The approach to creating a bio-bibliographic lexicon with examples from the book Bakarski zaslužnici u 19. i 20. stoljeću (Libellarium: journal for research in the field of information and related sciences, 2024)
Purpose. The aim of the paper is to provide insight into the lexicographical principles and theoretical foundations for compiling biographical and bibliographical dictionaries.Approach/Methodology/Design. The paper is based on a review and evaluation of relevant lexicographic literature, as well as the authors’ experience and strategies for addressing the challenges encountered in the writing of the book Bakar Meritorious Persons (Bakar: Grad Bakar, 2023). Detailed examples of the structural components of dictionary entries have been presented and explained. Additionally, the process of collecting and verifying entry information is outlined, with particular emphasis on cooperation with heritage institutions, relatives of meritorious individuals and cognizants.Practical implications. This paper is intended not only for future authors of similar works but also for students of information science, librarianship, and archival studies, offering them an understanding of the complexity of the theoretical framework and practical procedures involved in creating biographical dictionaries. This refers both to the applied methodology and the strategies used by the authors to address various dilemmas.Originality/Value. The originality of the paper lies in its presentation of theoretical insights into lexicographic heuristics while illustrating both the procedure and the techniques for compiling a local biographical dictionary. Numerous examples provided may serve as a guideline to future authors in structuring their lexicographic entry formats.
Keywords: biographic dictionary; biographic entry; Bakarski zaslužnici; lexicographic heuristics